The Influence of Family and Teacher Factors on Early Disruptive School Behaviors: A Latent Profile Transition Analysis. (June 2016) - Racz, Sarah J.; O'Brennan, Lindsey M.; Bradshaw, Catherine P.; Leaf, Philip J.
The kindergarten year plays an important role in establishing children's academic, social, and behavioral adjustment. Early identification of children who experience difficulties with the kindergarten transition is crucial to prevent continued behavioral and emotional problems. Family and school predictors of these early behavioral patterns can suggest important targets for preventive interventions. The current study examined heterogeneity in 2, 814 children's disruptive behaviors over the course of the kindergarten school year using latent profile and transition analyses. We further investigated the degree to which changes in these behavioral patterns varied as a function of family and teacher factors. Results provided evidence of three distinct profiles of disruptive behavior exhibited by kindergarteners (well-adapted, concentration problems, and at-risk), which were relatively stable over the course of the kindergarten school year. These behavioral patterns were associated with family (i.e., family problems, family involvement) but not teacher (i.e., efficacy and burnout) factors. Findings have important implications for the early identification of children at-risk for behavioral problems.